Germany : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that Germany's economic rebound of 2010-11 gave way to weakening momentum during the course of 2012. Although exports to non-European trading partners began to recover by mid-2012, in line with improved prospects in the United States and emerging economies, exports to the rest of the euro area continued to decline as the recession in the region continued. Consumption grew robustly as German unemployment remained near post-reunification lows. The outlook for the remainder of 2013 and 2014 is heavily dependent on a gradual recovery in the rest of the euro area and a sustained reduction in uncertainty.